2014
DOI: 10.1353/bsr.2014.0003
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Have a Problem With It, But Other Guys Do”: An Exploration of Condom Negotiation among Young Black Men Who Have Sex with Men in the South

Abstract: Condom negotiation among young Black men who have sex with men in the Southern United States was explored using the theory of reasoned action. Fifty-four (18- to 29-year-old) males participated in nine focus group interviews. Discussions elicited condom use and negotiation attitudes, beliefs and social norms. Positive personal attitudes (respect of self, personal health concerns) and high negotiation self-efficacy was emphasized. Conversely, social norms revealed non-prioritized condom use behavior. Divergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Many existing treatment programs focus on individual behavioral change. Yet, recent studies have shown that if we are to impact individuals sexual risk behaviors, the most effective and lasting impacts may come from interventions to substance use networks (Friedman et al, 2009) and community movements for social justice (Melton, 2014). This is especially true for black young adults, as previous research has shown that individual behavior alone does not account for the different rates of HIV and STI infections between blacks and whites.…”
Section: Resultsmentioning
confidence: 99%
“…Many existing treatment programs focus on individual behavioral change. Yet, recent studies have shown that if we are to impact individuals sexual risk behaviors, the most effective and lasting impacts may come from interventions to substance use networks (Friedman et al, 2009) and community movements for social justice (Melton, 2014). This is especially true for black young adults, as previous research has shown that individual behavior alone does not account for the different rates of HIV and STI infections between blacks and whites.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this study identified a population that, despite experiences with antihomosexual attitudes, has positive attitudes toward condom use and HIV prevention such as HIV testing. 25 The social norms of the local community conflict with these beliefs, implying the influence of external and cultural factors that should be considered in future research. Given the potential benefits of providing social, cultural, and community support as a strategy to decrease the prevalence of HIV and IPV, public health scientists should consider collaborative efforts as an approach to developing tailored interventions for young Black MSM in Mississippi.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 73 codes were finalized and used by the data analysts to create patterns and identify themes in the data. 25,26 The study protocol was approved by the Institutional Review Board of the University of Kentucky.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of research on sexual and ethnic minority HIV volunteers (Jennings & Andersen, 2003; Harris, 2014; Melton, 2014; Tester, 2004). Nonetheless, research concerning HIV volunteers who identify as sexual and ethnic minorities is still fairly rare (Swank & Fahs, 2013).…”
mentioning
confidence: 99%